2017
DOI: 10.1108/ijsi-05-2016-0019
|View full text |Cite
|
Sign up to set email alerts
|

High-rise building subjected to excessive settlement of its foundation: a case study

Abstract: Purpose Differential settlement between foundations’ elements induces additional stresses in the structural elements. In general, the amount of settlement that a structure can undergo without distress is large, provided that the structure settles uniformly. However, based on the fact that the soil under the foundation may not be uniform in nature and the loads transferred from the superstructure to the foundation are variable, differential settlements between the foundation elements are expected. The purpose o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…The effects of differential settlement on the magnitude of the bending moments, shear forces and stresses it generates in an RC frame building was further investigated by Lin et al (2015Lin et al ( , 2017. They reported that a frame building behaves elastically up to a differential settlement of 25mm and found that the downward displacement of the center column is the most critical case.…”
Section: Numerical Modelingmentioning
confidence: 99%
See 3 more Smart Citations
“…The effects of differential settlement on the magnitude of the bending moments, shear forces and stresses it generates in an RC frame building was further investigated by Lin et al (2015Lin et al ( , 2017. They reported that a frame building behaves elastically up to a differential settlement of 25mm and found that the downward displacement of the center column is the most critical case.…”
Section: Numerical Modelingmentioning
confidence: 99%
“…It was reported in Lin et al (2015Lin et al ( , 2017 that the settling column only affects the beams immediately attached to it. Therefore, only the four beams around column C-3 in the buildings are examined in this study.…”
Section: Bending Moment In the Beamsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the current emphasis on the construction industry, many domestic and foreign research teams have begun to impact settlement building in-depth study. Lin [2] used a bottom center column to distribute an excessive differential settlement of up to 75 mm to assess the stresses caused by excessive differential settlement in a typical tenstory reinforced concrete building. e analysis of damage and the resulting management of the built environment often requires high costs due to the establishment of reliable predictive models and the amount of data required to define the most appropriate repair work [3].…”
Section: Introductionmentioning
confidence: 99%